Pictorial (multimodal) metaphor in printed advertising - Juzelėnienė, Saulė; Šarkauskienė, Skirmantė (Lietuvių kalba, 2011)
The theoretical basis of the article is the methodology of pictorial/visual metaphor research presented in Charles Forceville’s work Pictorial Metaphor in Advertising (2006) and multimodal metaphor research proposed in his book Multimodal Metaphor (2009). Both verbal and non-verbal metaphors are investigated combining interaction theory proposed by Max Black and the principles of conceptual metaphor analysis formulated in cognitive linguistics. In a metaphor, the primary and the secondary subjects are considered equal to the target and the source domains distinguished by cognitive linguists and the result of their interaction (the properties of the secondary subject (source domain) are mapped onto the primary subject (target domain)) is a conceptual metaphor. The target domain in advertising is an item or service being promoted, while the source domain is an object whose properties are attributed to the item or the service being advertised. In the discourse of advertising metaphor is realised by verbal and non-verbal forms of communications: written language, spoken language, image, music, sound, gestures. If the target and source domains in a conceptual metaphor are expressed by means of one of the indicated forms, it is treated as a monomodal metaphor, whereas if they are expressed by more than one of them, it is regarded as a multimodal metaphor. Since in the case of pictorial metaphor one of the components is expressed verbally and the other – by means of an image, it is treated as one of the varieties of multimodal metaphor. In Lithuanian printed advertising, pictorial metaphor is used to express various concepts. In the article the following examples of conceptual metaphors are analysed: JUICE IS SUN, CAR IS ANIMAL, TILE ADHESIVE IS BINDWEED, VODKA IS A NATION/PERSON. The research has revealed that in a metaphor both the source and the target domain can be expressed using pictorial and verbal means and sometimes using both of them. As a result, both verbal and pictorial means are equally important in metaphor as their interaction makes an advertisement more persuasive and effective.